Specific Digitalization's Effect on Corporate ESG Performance: China's National Pilot Zone as Evidence - Ghaffar, Abdul; Asif, Muhammad (Journal of Environmental and Energy Economics, 2024)
Companies now have to deal with increasingly complicated and wide-ranging social duties in light of the real economy's deep integration and the fast expansion of digitalization. This research builds a double-difference model and applies it to China's National Prototype Area for the Progressive Growth of the Digital Economy to empirically examine how regional digitalization affects companies' ESG performance. The data used in the analysis is from 1178 A-share listed companies in the Shanghai and Shenzhen markets from 2013 to 2022. This study discovered that by increasing risk resilience, increasing the number of social contributions, and boosting corporate environmental information disclosure, regional digital construction may enhance corporate ESG performance. Furthermore, the improvement of digital construction on business ESG performance is more evident in regions where public environmental concerns are stronger. In addition, companies with higher executive environmental awareness than lower executive environmental awareness saw a greater contribution from regional digital construction to corporate ESG. In addition, this paper addresses the criticisms leveled at corporate environmental and social responsibility (ESG) by confirming that the disclosure of corporate ESG reports is driven more by corporate sustainability than by self-serving management, as measured by the company's real environmental behavior and information manipulation. Promoting businesses' active engagement in ESG practices via the potential of digital growth is crucial for developing nations.